Safety and tolerability of ledipasvir/sofosbuvir with and without ribavirin in patients with chronic hepatitis C virus genotype 1 infection: Analysis of phase III ION trials. Issue 1 (1st June 2015) - Alqahtani, Saleh A.; Afdhal, Nezam; Zeuzem, Stefan; Gordon, Stuart C.; Mangia, Alessandra; Kwo, Paul; Fried, Michael; Yang, Jenny C.; Ding, Xiao; Pang, Phillip S.; McHutchison, John G.; Pound, David; et al.
Abstract : In phase III studies, treatment with the once‐daily fixed‐dose combination tablet of ledipasvir/sofosbuvir (LDV/SOF) with and without ribavirin (RBV) resulted in high rates of sustained virological response (SVR) in patients chronically infected with genotype 1 hepatitis C virus, including those with compensated cirrhosis. We conducted an analysis of data from these trials to compare the safety and tolerability profile of LDV‐SOF with and without RBV. We analyzed treatment‐emergent adverse events (AEs) and laboratory abnormalities in patients who were randomized to 8, 12, and 24 weeks of LDV/SOF with or without RBV. In total, data from 1, 952 patients (of whom 872 received LDV/SOF with RBV and 1, 080 received LDV/SOF alone) were analyzed. Overall, 308 patients (16%) were African American, 224 (11%) had compensated cirrhosis, 501 (26%) had a body mass index ≥30 kg/m 2, and 440 (23%) were treatment experienced. Treatment‐related AEs occurred in 71% and 45% of patients treated with and without RBV, respectively, including fatigue, insomnia, irritability, and rash/pruritus. Patients receiving RBV with LDV/SOF were more likely to require dose modification, interruptions of treatment resulting from AEs, or require the use of concomitant medications than those receiving LDV/SOF alone. Rates of treatment‐related serious AEs and discontinuations resulting from AEs were similarly low (<1%) in both groups. The rate of SVR in those receiving RBV and those not receiving RBV was the same (97%). Conclusion : LDV/SOF plus RBV was associated with a greater incidence of AEs as well as concomitant medication use than LDV/SOF alone. Use of RBV did not impact the efficacy of LDV/SOF regimens in the ION phase III studies. (Hepatology 2015;62:25‐30)